Determining Effects of %wt Variation and Retention Rate of Reinforcement on the Mechanical Property of the Ceramic Reinforced Aluminum Matrix Composites - Jigar Suthar; Kaushik Patel (Recent Progress in Science and Technology Vol. 8, 2023)
Composites are one of the necessities of the current industrial infrastructure due to changing consumer demands. . Aluminum ceramic composites are among the most useful composites in the automotive and aeronautical industries due to their enhanced mechanical and thermal properties. The properties of the composite material, however, are significantly influenced by the amount of reinforcement. In this study, Al-SiC (Aluminum-Silicon Carbide) metal matrix composite was fabricated using a stir casting method. During the process, parameters such as stirring speed and temperature were kept constant. Sic particles with a mesh size of 200 were used in various proportions. The amount of reinforcement was varied from 0% to 12.5%. The hardness test, microstructure analysis, optical Emission Spectroscopy (OES), and SEM-EDX were used to investigate the effect of the percentage variation of the composite. The OES, microstructure analysis, and SEM-EDX results show that SiC is retained in pure aluminum. The SEM-EDX of the composite with the 7.5% SiC addition shows 5.94% SiC retention, indicating a 79% process efficiency. Furthermore, the hardness analysis revealed that increasing the percentage of SiC increases hardness. Optical Emission Spectroscopy (OES) and EDS outcomes show the presence of iron [Fe] from stirrer blade material.